Role of polyphenol oxidase, peroxidase and total phenol content in differential resistance of Dioscorea species to Fusarium moniliforme - YUBEDEE, A G (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted to find out the possible relationship between phenolic contents and peroxidase activities of different Dioscorea spp to Fusarium moniliforme Sheldon. Dioscorea cayenensis Lam and D. dumelorum (Knuth) Pax had very high content of polyphenol oxidase. peroxidase and total phenol was resistant to F moniliforme. D. rolundata Pair, D. alata L. and D. esculenta (Lour) Burk had low contents of polyphenol oxidase, peroxidase and total phenol contents and were susceptible to F moniliforme. Phenolic contents and peroxidase activities decreased with increase in the age of yam tubers with the increase in rate of of infection. There was a sharp rise in the amount of phenolic compounds and peroxidase activities at the start of the infection. They later dropped as the infection progressed.